2018 EHRA expert consensus statement on lead extraction: recommendations on definitions, endpoints, research trial design, and data collection requirements for clinical scientific studies and registries: endorsed by APHRS/HRS/LAHRS - Bongiorni, Maria G; Burri, Haran; Deharo, Jean C; Starck, Christoph; Kennergren, Charles; Saghy, Laszlo; Rao, Archana; Tascini, Carlo; Lever, Nigel; Kutarski, Andrzej; Fernandez Lozano, Ignacio; Strathmore, Neil; et al. (Europace (London, England), 2018)
The number of cardiac implantable electronic device (CIED) implantations has increased over recent years as a result of population growth, increasing life expectancy, adoption of guidelines, and better access to healthcare. Transvenous lead extraction (TLE), as a part of an overall lead management strategy, has also been increasing, not only as a consequence of this growth, but also because of increasing rates of infection, lead failure, awareness of indications for lead management, and development of extraction tools. Clinical research is essential for understanding efficacy and risks of TLE, which has important implications regarding decision-making and therapeutic strategies in patients who are candidates for this procedure. Data on TLE have mainly come from retrospective series, with variable reporting of endpoints. Recently, the ELECTRa registry conducted by the European Heart Rhythm Association (EHRA), has reported the largest prospective experience on lead extraction published to date in 3555 patients recruited from 19 European countries. There remain unresolved issues, which is a strong incentive for conducting further specifically-designed clinical trials to answer important questions in this area. In addition to clinical studies, national registries are potentially useful for evaluating epidemiology of TLE as well as for quality control and understanding resource implications. Standardization of definitions and reporting of parameters are paramount in order to analyse, compare, and pool data for scientific purposes. Expert consensus statements on lead extraction have been published by the Heart Rhythm Society (HRS) in 2009 and 2017, and by EHRA in 2012. Experience from the ELECTRa registry has been valuable for identifying challenges faced with conducting scientific studies in this field, and provides a framework for future endeavours. This writing group has been commissioned by EHRA to provide recommendations for designing scientific studies, reports and registries relating to lead extraction.